Factors Affecting Reuse Intention on Mobile Shopping Application - Nadi Afira; Elevita Yuliati (IPTEK Journal of Proceedings Series, 2019)
Mobile apps have become a game changer in retail business. Consumers can shop anything through their smartphones anytime and anywhere. In Indonesia, various of online marketplaces such Tokopedia, Lazada, and Shopee have emerged giving customers many options to shop and they tend to switch channel easily to another shopping apps. This study tested a conceptual model describing the relationships among Technology Acceptance Model (TAM), flow, attitude towards mobile shopping apps and intention to reuse mobile shopping apps. The sample of this research is consumers who have experienced online shopping using mobile shopping apps. The data were collected from 181 respondents via online questionnaire survey. Structural Equation Modeling (SEM) was used for data analysis using AMOS version 22. The results show that perceived usefulness is signiﬁcantly has a positive impact to ﬂow while perceived ease of use is not significantly related to flow. Flow is positively related to attitude. In addition, the results indicated that attitude is one of the main predictors of consumers reuse intention towards mobile shopping apps and has a greater impact than the direct relation of perceived usefulness to reuse intention. This study extends the research scope of mobile shopping behavior and provided implications for mobile app retailing